Making sense of pedagogy in a world of uncertainty - Blessinger, Patrick (Revista Perspectivas Educacionales (REPED), 2025)
During an age of accelerating technology, social upheaval, and environmental vulnerability, the art and science of pedagogy can't be summed up simply as a method of teaching but rather as a multi-dimensional, fluid, and uniquely human pursuit. As explored in my article, Making Sense of Pedagogy (Blessinger, 2020), pedagogy is both a philosophy and a praxis—a way of seeing the world, relating to others, and shaping futures through deep learning. To rethink pedagogy today is to engage with the very essence of what it means to teach and learn in a hyperconnected and unpredictable world. This rethinking is not optional; it is urgent. In the span of the last 200 years, we have seen the global literacy rate go from about 10% to nearly 90%. This demonstrates the importance of literacy, and teaching and learning, in contemporary life. (Ir a traducción del artículo completo)